2021
DOI: 10.11648/j.ajpb.20210603.12
|View full text |Cite
|
Sign up to set email alerts
|

Genotype X Environment Interaction and Stability Analysis for Grain Yield of Bread Wheat (<i>Triticum aestivum</i>) Genotypes Under Low Moisture Stress Areas of Ethiopia

Abstract: A multi-locations' experiments were carried out from 2018 to 2019 main cropping seasons in moisture stress areas of Ethiopia to estimate the genotype x environment interaction and to select stable and adaptable variety/ies for grain yield of bread wheat. The genotypes consisted of 23 genotypes and two standard checks arranged in alpha lattice design replicated three times. Data were taken for agronomic traits and diseases. Analysis of variances and stability analysis were carried out for grain yield using R so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
1
0
0
Order By: Relevance
“…In this study, the wheat genotypes PBW 750, DPW 621-50, WH 542, PBW 486, PBW 661 and WH 1192 were identified as stable genotypes in yield, and the genotypes HD 2967, WH 1151, UP 2660, PBW 676, WH 1182, PBW 729, WH 1061, PBW 560, PBW 725 and PBW 721 were unstable. Similar to this research, Dabi et al [35] also identified high-yielding and stable genotypes ETBW 9080, ETBW 9172, ETBW 9646, ETBW 9396, ETBW 9452, ETBW 9136 and ETBW 9139, inferring little interaction with the environment. Genotypes HD 2967, WH 1151, UP 2660 and PBW 676 far from the IPCA origin appeared to be adapted to a timely sown rainfed environment, whereas the genotypes WH 1182 and PBW 729 were specially adapted to a timely sown irrigated environment.…”
Section: Discussionsupporting
confidence: 81%
“…In this study, the wheat genotypes PBW 750, DPW 621-50, WH 542, PBW 486, PBW 661 and WH 1192 were identified as stable genotypes in yield, and the genotypes HD 2967, WH 1151, UP 2660, PBW 676, WH 1182, PBW 729, WH 1061, PBW 560, PBW 725 and PBW 721 were unstable. Similar to this research, Dabi et al [35] also identified high-yielding and stable genotypes ETBW 9080, ETBW 9172, ETBW 9646, ETBW 9396, ETBW 9452, ETBW 9136 and ETBW 9139, inferring little interaction with the environment. Genotypes HD 2967, WH 1151, UP 2660 and PBW 676 far from the IPCA origin appeared to be adapted to a timely sown rainfed environment, whereas the genotypes WH 1182 and PBW 729 were specially adapted to a timely sown irrigated environment.…”
Section: Discussionsupporting
confidence: 81%